2008
DOI: 10.1007/s00497-008-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-pollination hybridization barriers in Nicotiana section Alatae

Abstract: Nicotiana section Alatae contains eight species with variable flower sizes and morphologies. Section members readily hybridize in the glasshouse, but no hybrids have been observed in natural sympatric and parapatric populations. To investigate interspecific crossing relationships with respect to mechanisms preventing hybridization, all members of section Alatae were intercrossed in a complete diallel. We found positive correlation between the pistil length of the pollen donor and interspecific seed set relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 75 publications
(90 reference statements)
5
59
0
Order By: Relevance
“…10 days after pollination, only a few developed to globular stage and aborted thereafter. Thus there are evidently severely post-zygotic barriers preventing the hybridization of chrysanthemum 'Zhongshanjingui' and mugwort 'Variegata', just as affect many wide crosses (Weiblen and Brehm 1996;Lee et al 2008;Tang et al 2009). However, the ability of some hybrid embryos to develop normally up to the globular stage indicated that there was a possibility of overcoming the cross barriers using ovule culture (Li and Chen 2004;Tang et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…10 days after pollination, only a few developed to globular stage and aborted thereafter. Thus there are evidently severely post-zygotic barriers preventing the hybridization of chrysanthemum 'Zhongshanjingui' and mugwort 'Variegata', just as affect many wide crosses (Weiblen and Brehm 1996;Lee et al 2008;Tang et al 2009). However, the ability of some hybrid embryos to develop normally up to the globular stage indicated that there was a possibility of overcoming the cross barriers using ovule culture (Li and Chen 2004;Tang et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…However, as Darwin concluded (1884), there are many exceptions to this tenet, both within heterostyled species where pollen grain size can be identical in the two morphotypes, and between species wherein pollen grains are similarly sized but must grow greatly varying distances in styles. While style length does not vary as much in the tomato clade as in some other taxa (Lee et al 2008), there is more than twofold variation in style length, from 5.35 to 11.76 mm, and threefold variation in pollen size (volume), from 4,419 to 13,388 lm 3 (Fig. 2).…”
Section: Floral Structuresmentioning
confidence: 94%
“…4D, 5A, and 6, A, E, F, and I). Perhaps, pollen tubes growing in planta may have a more extended growth region because of their much faster growth rates Lee et al, 2008a). Nevertheless, culture-grown tubes expressing NaPCCP::GFP displayed similar patterns to tubes grown in planta (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Pollen tubes attain remarkable growth rates in planta, as high as 250 nm s 21 in lily (Messerli et al, 2000) and 400 nm s 21 in N. alata (Lee et al, 2008a), rates much faster than growth in culture. Thus, the pistil promotes rapid pollen tube growth.…”
Section: Discussionmentioning
confidence: 99%